2007
DOI: 10.1016/j.lfs.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin peptides differentially regulate the human κ opioid receptor

Abstract: Dynorphins, endogenous peptides for the κ opioid receptor, play important roles in many physiological and pathological functions. Here, we examined how prolonged treatment with three major prodynorphin peptides, dynorphin A (1-17) (Dyn A), dynorphin B (1-13) (Dyn B) and α-neoendorphin (α-Neo), regulated the human kappa opioid receptor (hKOR) stably expressed in Chinese hamster ovary (CHO) cells. Results from receptor binding and [ 35 S]GTPγS binding assays showed that these peptides were potent full agonists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…However, disparate findings were obtained. Heikkila et al [402] reported enhanced CSF DYN A levels in unmedicated patients with schizophrenia relative to healthy and psychiatric controls using an antibody recognizing DYN A (9)(10)(11)(12)(13)(14)(15)(16)(17). CSF DYN A levels significantly correlated with increased psychotic rating scores on the Brief Psychiatric Ratings Scale.…”
Section: Csf and Tissue Levels Of Dyn In Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations
“…However, disparate findings were obtained. Heikkila et al [402] reported enhanced CSF DYN A levels in unmedicated patients with schizophrenia relative to healthy and psychiatric controls using an antibody recognizing DYN A (9)(10)(11)(12)(13)(14)(15)(16)(17). CSF DYN A levels significantly correlated with increased psychotic rating scores on the Brief Psychiatric Ratings Scale.…”
Section: Csf and Tissue Levels Of Dyn In Schizophreniamentioning
confidence: 99%
“…Other biologically active DYNs include DYN B1-13 (DYN B/rimorphin), DYN B1-29 (leumorphin), DYN A/B1-32 (big DYN) and a-and b-neoendorphin [10][11][12][13][14]. The affinity and efficacy of these peptides differ with DYN A being the most potent and b-neoendorphin the least [15,16]. Importantly, DYNs bind with high affinity to other opioid and non-opioid receptors (e.g., acid-sensing ion channels and NMDA receptors), [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After repeated or sustained exposure to agonists, KORs are desensitized by receptor phosphorylation and recruitment of β-arrestin and endocytosed via a clathrin-and dynamin-dependent pathway. These internalized receptors either return to the membrane by dephosphorylation and EBP50/NHERF-1-dependent recycling or are degraded via both lysosome and proteasome systems [15,16] . G-protein receptor kinase 3 (GRK3) and β-arrestin 1/2 play important roles in the modulation of KOR trafficking [12,17] .…”
Section: Introductionmentioning
confidence: 99%